If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 8(st + 3w) + 3st = 0 3 + (st * 8 + 3w * 8) + 3st = 0 3 + (8st + 24w) + 3st = 0 Reorder the terms: 3 + 8st + 3st + 24w = 0 Combine like terms: 8st + 3st = 11st 3 + 11st + 24w = 0 Solving 3 + 11st + 24w = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 11st + -3 + 24w = 0 + -3 Reorder the terms: 3 + -3 + 11st + 24w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 11st + 24w = 0 + -3 11st + 24w = 0 + -3 Combine like terms: 0 + -3 = -3 11st + 24w = -3 Add '-24w' to each side of the equation. 11st + 24w + -24w = -3 + -24w Combine like terms: 24w + -24w = 0 11st + 0 = -3 + -24w 11st = -3 + -24w Divide each side by '11t'. s = -0.2727272727t-1 + -2.181818182t-1w Simplifying s = -0.2727272727t-1 + -2.181818182t-1w
| 16=3-7k-1 | | 15p+19q+p-3q-6p= | | 3x-2x+7=15 | | 12-4p=-4-6p | | 4cos^2x+4sin-1=0 | | 6.2(a+b)+2.6(a+b)+3a= | | 8t^2+3t+24=0 | | t/3-4=9 | | 8m=-12+5m | | 3x+2y+4(3x+y)= | | 2+(x+3)= | | 11*y=-22 | | 4x+3x+28=2 | | -9+5=-22 | | 6(x+2)+3(3x+7)=4(5+4x)-7 | | 7+3(uv-6)+u= | | r-8=9 | | C^2-14c+49=0 | | 50=d-0.5d | | 21-14x=29+12x | | y=7/3(-3)+5 | | 4(2x+y)+5x= | | 20-5(p+1)+3p=(2p-15) | | -x+(-2x)= | | 8(4-3x)+7(x-3)+3(9+7x)=10 | | 8=5-1/6x | | 8q+5r-7q-6r= | | 4z=13-21 | | 100-y^2=0 | | x+4x=14.95 | | x+4x=14.995 | | 2x-3+x+2x-4=38 |